Aging Features and Strength Model of Diorite’s Damage Considering Acidization - Chen, Wei; Wan, Wen; Zhao, Yanlin; Xie, Senlin; Jiao, Bing; Dong, Zhenming; Wang, Xianqing; Lian, Shuailong (Frontiers in Physics, 2020)
Acidic fluids will cause rock erosion and further endanger the safety of rock engineering. To explore the aging characteristics of the mechanical damage under acid condition, diorite specimens were saturated in neutral water and acid solutions with pH values of 3 and 5 for 49 days. The masses and sizes of the specimens and the pH values of the acidic solution were tracked and measured. Besides, the specimens before and after saturations were observed by an electron microscope scanner. Meanwhile, triaxial compression tests were carried out under neutral water, pH = 5 and pH = 3 hydrochloric acid solutions, respectively. The mass damage features and mechanical properties of diorite specimens saturated in solutions with different pH values were analyzed. The results show: (1) after acidic saturation, the original lamellar structures and crystal forms were spongy or flocculent. The structure loosened and the boundary between layers became fuzzy. Meanwhile, the number of micro-cracks and micro-pores increased, which weakened the macro-mechanical performances of diorite; (2) the acid condition with pH value of 3 could be used to simulate the long-term effect of the weakly acidic environment in nature; (3) internal friction angle of diorite was more sensitive to acidic solutions than its cohesion; (4) at the initial stage of saturation, diorite broke rapidly. With increasing saturation time, the damage rate slowed down and finally stabilized. The established damage strength model considering acidification could properly describe the test results.